FACTORS AFFECTING ONLINE PURCHASE INTENTION AND PURCHASE DECISION OF ORGANIC VEGETABLES: A CASE STUDY OF AGRIOO SEMARANG PLATFORM - Fajri F.N.; Ekowati T.; Setiadi A. (Russian Journal of Agricultural and Socio-Economic Sciences, 2023)
Organic vegetables are commonly found in shopping centers and supermarkets but are difficult to find in traditional markets, so it is difficult for people to reach them. Now a new method of selling organic vegetables through online platforms has been developed, making it easier for consumers to reach. The opportunity for marketing organic vegetables online is very large nowadays, especially since the use of the internet in Indonesia is always increasing from year to year. Purchasing in e-commerce will also make it easier for consumers to choose the organic vegetables they need. One of the online platforms for shopping for organic vegetables in Semarang is AGRIOO. Purchase intention in a web-shopping environment will determine the power of consumers to make purchases online. This study aims to analyze the factors that influence the intention and purchase of organic vegetables at AGRIOO Semarang City. This study uses the SEM-PLS method. The results showed that the quality of information affects purchase intention with a p-value of 0.001 <0.5. The study also shows the results that attitude variable (0.000), e-WOM (0.012), and price perception (0.003) affect purchase intention and purchase intention (0.000) affects consumer purchase decisions. The system quality does not affect purchase intention.